2013
DOI: 10.1111/1462-2920.12311
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns in microbial communities inhabiting the hot springs of Tengchong, Yunnan Province, China

Abstract: Studies focusing on seasonal dynamics of microbial communities in terrestrial and marine environments are common; however, little is known about seasonal dynamics in high-temperature environments. Thus, our objective was to document the seasonal dynamics of both the physicochemical conditions and the microbial communities inhabiting hot springs in Tengchong County, Yunnan Province, China. The PhyloChip microarray detected 4882 operational taxonomic units (OTUs) within 79 bacterial phylum-level groups and 113 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 45 publications
5
73
1
Order By: Relevance
“…Supporting our assumption that hot springs of this nature are low in biomass, a recently concluded PhyloChipbased study reported the presence of only 4882 OTUs associated with a Chinese hot spring (Briggs et al, 2013). As documented previously in Thailand's Bor Khlueng neutral pH hot spring systems (50-57°C), members of major phyla were well represented in the P1, P2, and P3 samples (Kanokratana et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Supporting our assumption that hot springs of this nature are low in biomass, a recently concluded PhyloChipbased study reported the presence of only 4882 OTUs associated with a Chinese hot spring (Briggs et al, 2013). As documented previously in Thailand's Bor Khlueng neutral pH hot spring systems (50-57°C), members of major phyla were well represented in the P1, P2, and P3 samples (Kanokratana et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…As a result, the formate and acetate assimilation and mineralization activities reported here may be more appropriately referred to as rate potentials rather than absolute rates. A further consideration which is supported by repeated sampling of hot springs over seasonal or annual cycles is that the concentrations of organic substrates vary temporally (25,47). This variability makes the estimation of representative substrate transformation rates more difficult and potentially less meaningful, as these rates likely vary to a large degree in accordance with variations in the mode and magnitude of delivery of organic substrates to these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that this is mainly due to differences in the pH, temperatures and TOC between the two springs (Hou et al 2013). The effect of seasonal changes on the microbial diversity in Tengchong hot springs, which are located in a subtropical area with heavy temporal monsoon rain fall, has been studied by Briggs et al (2014) and Wang et al (2014). Specifically, they compared the samples collected between June and August (rainy season) with those of Hou and colleagues sampled in January during the dry season.…”
Section: Tengchong Chinamentioning
confidence: 99%